PENINGKATAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW KELAS V TEMA 6 PANAS DAN PERPINDAHANNYA SUB TEMA SUHU DAN KALOR DI SD INPRES OEPOI - Ronaldo Berto Bili; Budi Kurniawan (Mimbar PGSD Flobamorata, 2023)
This research is motivated by the students' critical thinking skills are still low in grade V SD Inpres Oepoi in science learning, from pre-cycle observations the teacher has used the learning model but the students' scores have not reached the KKM 70. students' critical thinking skills through the jigsaw type cooperative learning model class V theme 6 heat and its transfer sub-theme temperature and heat at SD Inpres Oepoi. To overcome these problems, classroom action research was conducted which aims to improve students' critical thinking skills in science subjects, theme 6 of heat and its transfer sub-themes of temperature and heat for class V SD Inpres Oepoi through the application of the Jigsaw type cooperative learning model. At the pre-action stage, based on the results of the research, students' critical thinking skills were still below the KKM 70 standard. In the first cycle test results, the average score obtained by students was 67%. In the second cycle the average value of students is 93% with the criteria of completeness that have reached the indicator of success, the average value is above the KKM 80% as much as > 85% of the total 15 students. The conclusion is that the application of the Jigsaw type cooperative learning model can improve students' critical thinking skills on theme 6 of heat and its transfer sub-themes of temperature and heat for class V SD Inpres Oepoi for the academic year 2021/2022.